TRP Channels as Drug Targets to Relieve Itch - Zili Xie; Hongzhen Hu (MDPI AG, 2018)
Although acute itch has a protective role by removing irritants to avoid further damage, chronic itch is debilitating, significantly impacting quality of life. Over the past two decades, a considerable amount of stimulating research has been carried out to delineate mechanisms of itch at the molecular, cellular, and circuit levels. There is growing evidence that transient receptor potential (TRP) channels play important roles in itch signaling. The purpose of this review is to summarize our current knowledge about the role of TRP channels in the generation of itch under both physiological and pathological conditions, thereby identifying them as potential drug targets for effective anti-itch therapies.